(Un)Obtainable Luxury and Performance: The Semiotics of Michael Jordan’s 1996 V12 Mercedes S600 Lorinser - Jacheć, Tomasz (Acta Neophilologica, 2022)
On August 23rd, 2020, a 1996 V12 Mercedes S600 Lorinser was sold at an eBay auction. While the asking price for this particular model, in 2020, was approximately between 4,500 and 11,000, this specific car was sold for the hefty sum of 202,200. What makes this Mercedes car unique and pricey is the fact that it used to belong to a basketball great, Michael Jordan. The timing of the auction in question, finalized in the midst of the global Coronavirus pandemic, and following the release of The Last Dance documentary on Jordan’s career, factors into the interpretation of the semiotics of the automobile itself. The aim of this article is to analyze: the semiotic dimension of Michael Jordan as a persona and a brand/sign; the semiotic dimension of the Mercedes brand and cars; and, ultimately, the semiotic dimension of the auction of Jordan’s 1996 V12 Mercedes S600 Lorinser in the context of time and selling price, with nostalgia as a factor, in order to examine the result of the synergy of “Jordan” and “Mercedes.”